Statistics and probability - Bahrom, Suhaila; Ibrahim, Dayana; Mat Zean, Hazaliza; Abu Hassan, Norafizah; Md Saad, Norlaili; Mat Yaacob, Siti Nubailah; Hisham, Balqis; Happas, A'fifah (IIUM PRESS, 2022)
Statistics and Probability is written for foundation level students, specifically biological module students at the Centre for Foundation Studies, IIUM, who are taking Mathematics II as one of their core subjects. This book also intended for students who do not have a strong background in Mathematics. The only prerequisite for this text is knowledge of elementary algebra. The goal of Statistics and Probability has been to make the subject of Statistics interesting and accessible to a wide and varied audience. The applications in this book includes problem in health, business, education, entertainment, political science, psychology, history, transportation, physical sciences, travel and leisure. The content of this book covers topic such as Introduction to Statistics, Counting Rules and Probability, Discrete Probability Distributions, The Normal Distribution, Sampling Distribution, Confidence Interval and Introduction to Hypothesis Testing.